Prilocaine 2% for Spinal Anesthesia in Incarcerated Inguinal Hernia Surgery with Congestive Heart Failure - Koeshardiandi, Mirza; Bisama, Pandhu Mahendra; Gibran, Dian Muhammad (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Congestive heart failure (CHF) is a disease caused by abnormalities in the myocardium. This abnormality reduces the heart's ability to pump blood throughout the body. Anesthetic drugs have a major cardiovascular effect under general and regional anesthesia. Objective: This study aims to examine the effect of prilocaine as a subarachnoid block regional anesthetic drug in patients undergoing non-cardiac surgery with comorbid heart failure. Case Report: A 59-year-old man came complained of a lump in his left upper groin that had been present since a day before his admission to the hospital. The lump could not be inserted. The patient felt pain in the lump area with a visual analog score (VAS) of 7-8. His blood pressure was 138/84 mmHg, pulse rate was 104 times per minute, respiration rate was 22 times per minute, temperature was 36oC for axillary measurement, oxygen saturation was 92% based on room oxygen, and VAS was 7-8. The abdominal examination revealed a lump in the patient's left upper groin that could not be reinserted, hyperemic, and painful when pressed. With an EF Teich of 17.1%, the echocardiographic examination revealed that the dimensions of the patient's heart chambers (RV and LV dilatation) and LV systolic function had decreased. Conclusion: Stable hemodynamics in non-cardiac surgery with a relatively short duration is the main choice for HF patients. Spinal anesthesia with a regimen of 2% prilocaine at a dose of 80 mg plus 0.1 mg morphine resulted in stable hemodynamics and low pain scores in patients with comorbid congestive heart failure undergoing non-cardiac surgery.